Breast augmentation with autologous fat grafting: literature review and case report - Chang Yung Chia (Revista Brasileira de Cirurgia Plástica, 2016)
INTRODUCTION: The technique and technology lipoaspirate autotransplantation to the breast with the aim of aesthetic appearance and reconstruction has strongly advanced; further, its acceptance by doctors and patients has also improved. The author reports cosmetic breast augmentation and performed a literature review, focusing on the efficacy, carcinogenic potential, and imaging diagnosis. METHOD:A literature review was performed using English-language articles from the PubMed database and the Brazilian Journal of Plastic Surgery (RBCP); in addition, case series of the initial experience of the author has been described. RESULTS: The volume remained stable from the second month, and there were no postoperative complications. Imaging did not show any pathological alterations. In all, 24-related articles were selected. DISCUSSION: Among the 24 articles, only two prospective non-controlled studies were found, but overall, imaging diagnostic tests did not reveal problems, the carcinogenic potential was not increased, and case series had positive results. CONCLUSION: The procedure is reproducible, safe and effective, and reinforces the use of this technique in breast reconstruction and as an option in cosmetic breast augmentation. However, it may require a longer learning curve to avoid complications and achieve good results.